2003
DOI: 10.1515/znc-2003-9-1018
|View full text |Cite
|
Sign up to set email alerts
|

GC/MS Analysis of Some Bioactive Constituents from Carthamus lanatus L.

Abstract: Sterols, triterpenes, volatiles, polar and other constituents in aerial parts of Carthamus lanatus were analyzed by gas chromatography-mass spectrometry. Over 90 compounds were identified most of them new for the species. Sitosterol and stigmasterol were the most abundant of 10 sterols identified in the sterol fraction. Taraxasterol, α-and -amyrine prevailed in the triterpene fraction. Volatiles, sterols and a fraction of the dichloromethane extract showed strong cytotoxicity (Artemia salina assay).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Triterpenes attract attention because of their biological activity 15 . Squalene is a triterpene and has been reported in to have antimicrobial activity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Triterpenes attract attention because of their biological activity 15 . Squalene is a triterpene and has been reported in to have antimicrobial activity 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Previously, Mitova et al . [11] isolated dehydroabietylic acid from the aerial part of C. lanatus and dehydroabietylamine from the Rosin plant. [3839] In the present investigation, we have isolated dehydroabietylamine from the leaves of C. tinctorius .…”
Section: Discussionmentioning
confidence: 99%
“…[6] Phytochemical studies of the species revealed the presence of sesquiterpene glycosides,[7] aromatic acids and serotonins,[8] flavonoids[910] and sterols and triterpenes. [11] The pharmacological properties of safflower have been evaluated for antitumor, sedative,[12] antimicrobial,[13] antiinflammatory and analgesic effects. [14] Previously, Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…This metabolite was soluble in most organic solvents, such as methanol, ethanol, chloroform and ethyl acetate, but had poor solubility in water. Sitosterol and stigmasterol, the possible intermediates of stigmastan-3,5-diene, have been described as chemical defences against some bacterial and fungal pathogens (Kiprono et al 2000;El-Shazly et al 2002;Mitova et al 2003), and as inhibitors of DNA polymerase (Prakash Chaturvedula et al 2003;Li et al 2004). Additionally, Wang and Maas (1997), reported that strawberry roots resistant to Phytophthora fragariae have higher levels of sitosterol.…”
Section: Fractionsmentioning
confidence: 99%